The Influence of Free Wi-Fi And Music on Consumer Satisfaction in Coffee Shops Around Garuda Streat, Tambakrejo, Jombang - Muhamad Ja'far Sodiq; Septi Ambar Indraningtia Sukma; Yessita Puspaningrum (AGARICUS: Advances Agriculture Science & Farming, 2024)
This research aims to determine the influence of free Wi-Fi and music on consumer satisfaction. The research method used is a quantitative descriptive method. The data collection instrument used a questionnaire given to 90 respondents. Data were analyzed using multiple linear regression with the help of SPSS version 22 software. The independent variables of this research were free Wi-Fi and music, while the dependent variable was consumer satisfaction in coffee shops around Garuda Streat, Tambakrejo, Jombang. Results all statements are valid, reliable and pass the classical assumption test. Based on the results of the tests carried out, the variables free Wi-Fi and music have a partial positive effect on consumer satisfaction with regression coefficient values ​​of 0.588 and 0.160 respectively. The free Wi-Fi variable has a significant effect on consumer satisfaction with a Sig value. 0.006 < 0.05 or t count 2.381 > t table 1.988. Meanwhile, the music variable has no significant effect on consumer satisfaction with the Sig value. 0.110 > 0.05 or calculated t value 1.617 < t table 1.988. The free Wi-Fi variable and the music variable simultaneously have a significant effect on the consumer satisfaction variable, because the Sig. value is 0.000 < 0.05 or the calculated F value is 10.753 > F table 3.100. According to the R Square value, it can be concluded that from the 100% figure, 19.8% of the free Wi-Fi and music variables simultaneously / together influence the consumer satisfaction variable, while the remaining 80.2% is influenced by other variables outside the model.